Continuous riverine biodiversity changes in a 10‐years‐post‐restoration‐study—Impacts and pitfalls. (24th September 2020) - Lorenz, Armin W.
Abstract: Evaluating river restoration effects over several years is the exception rather than the rule. The benthic invertebrate fauna of three small mountain streams was investigated yearly from 2010 to 2019 following remeandering measures. Additionally, upstream near‐natural reaches were studied following a Before‐After‐Control‐Impact (BACI) design. Species richness and Ephemeroptera, Plecoptera and Trichoptera richness decreased strongly immediately after restoration but had positive effect sizes in the following 6 years. Abundances increased in all sites after restoration. These patterns were consistent also in the upstream near‐natural reaches, except for the decrease in richness in the second year, indicating that other factors beside the restoration affected the sites. A large flood event coincided with the implementation of the restoration measures depleting also the near‐natural sites. The similarity between paired reaches showed a sharp decline in the first year after restoration, followed by a direct increase, which indicates fast recolonization from the upstream reaches. Community composition analysis showed a shift of all communities with the time axis, underlining a substantial effect of external factors. Generalized linear mixed effects models exhibited that the percentage of tree cover and riparian vegetation had significant effects on changes in richness and abundance. Clear‐cut logging in the floodplains to restore natural floodplain forest supposedly increased water temperatures because many cold‐adapted upstream species were replaced by species naturally inhabiting more downstream reaches. The results emphasize that multiannual samples and a BACI design are necessary to understand restored systems. Furthermore, floodplain restoration and natural hydrology often shape benthic invertebrate communities more than pure instream restoration measures.